Bone marrow aspirate: a viable source of stem cells for bone regeneration. A systematic review (Research, Society and Development, 2021)
This systematic review evaluated the effectiveness of bone marrow aspirate (BMA) to enhance bone repair in humans. Comprehensive survey of ramdomized clinical trials published up to June 2021 and listed in PubMed/MEDLINE, EMBASE, and Cochrane Library databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Two reviewers independently searched eligible studies, made a final article selection, and extracted the data of the selected studies to evaluate it qualitatively. Overall, 13 studies were included in the review. Experimental models involved Posttraumatical aseptic nonunions of long bones of the upper limb, alveolar ridges following tooth extraction, atrophic mandibular fracture, benign bone lesions, bilateral tibial lengthening, fracture of intracapsular neck femur, maxillary horizontal ridge augmentation, non-traumatic femoral head necrosis, and sinus maxillary augmentation. The analyses included radiography, tomography, biopsies, and clinical evaluations. Ten studies reported enahanced bone formation (primary outcome) with combined use or not of BMA with other biomaterials and three studies found no benefit resulting from the use of BMA to treat bony defects. Secundary outcomes related to the healing process were also evaluated and positive, such as postoperative complications and pain visual analogue score. Within the limits of the present study, it can be concluded that BMA can improve the early stages of bone healing process.